erception of preschool teachers of educational computer games and the development of socio-emotional competencies in preschool children - Stanojević, Anastasija S.; Stanisavljević Petrović, Zorica Č; Marković, Marija R (Norma, 2025)
Previous research regarding the effects of educational computer games on the socio-emotional development of preschool-aged children has mostly focused on the use of digital tools in older school-age children or adolescents, with fewer studies dedicated to preschool-aged children. The aim of this study is to examine teachers' perceptions of the impact of computer games on emotional regulation, social skills, as well as cooperation and teamwork skills in preschool-aged children. The study involved 188 teachers from Serbia, whose perceptions were analyzed in relation to their age, years of work experience, workplace, and level of education. Based on the results, it can be concluded that due to the inability to implement computer games because of the lack of digital equipment in institutions and the lack of experience, teachers are primarily indecisive, and then disagree when evaluating the positive effects of playing educational computer games on the social and emotional development of preschool-aged children. The cross-analysis of independent variables established that the only statistically significant determinant influencing teachers' views on the topic is their age, with older teachers generally having a more positive perception of the effects of educational games compared to younger teachers in the study sample.
Keywords: computer games; social development; emotional development; competencies; preschool age children